High density lipoprotein is targeted for oxidation by myeloperoxidase in rheumatoid arthritis - Vivekanandan-Giri, Anuradha; Slocum, Jessica L; Byun, Jaeman; Tang, Chongren; Sands, Robin L; Gillespie, Brenda W; Heinecke, Jay W; Saran, Rajiv; Kaplan, Mariana J; Pennathur, Subramaniam (Annals of the rheumatic diseases, 2013)
Objective Phagocyte-derived myeloperoxidase (MPO) and pro-inflammatory high density lipoprotein (HDL) associate with rheumatoid arthritis (RA), but the link between MPO and HDL has not been systematically examined. In this study, we investigated whether MPO can oxidise HDL and determined MPO-specific oxidative signature by apoA-1 by peptide mapping in RA subjects with and without known cardiovascular disease (CVD). Methods Two MPO oxidation products, 3-chlorotyrosine and 3-nitrotyrosine, were quantified by tandem mass spectrometry (MS/MS) in in vitro model system studies and in plasma and HDL derived from healthy controls and RA subjects. MPO levels and cholesterol efflux were determined. Site-specific nitration and chlorination of apoA-1 peptides were quantified by MS/MS. Results RA subjects demonstrated higher levels of MPO, MPO-oxidised HDL and diminished cholesterol efflux. There was marked increase in MPO-specific 3-chlorotyrosine and 3-nitrotyrosine content in HDL in RA subjects consistent with specific targeting of HDL, with increased nitration in RA subjects with CVD. Cholesterol efflux capacity was diminished in RA subjects and correlated inversely with HDL 3-chlorotyrosine suggesting a mechanistic role for MPO. Nitrated HDL was elevated in RACVD subjects compared with RA subjects without CVD. Oxidative peptide mapping revealed site-specific unique oxidation signatures on apoA-1 for RA subjects with and without CVD. Conclusions We report an increase in MPO-mediated HDL oxidation that is regiospecific in RA and accentuated in those with CVD. Decreased cholesterol efflux capacity due to MPO-mediated chlorination is a potential mechanism for atherosclerosis in RA and raises the possibility that oxidant resistant forms of HDL may attenuate this increased risk.